2002
DOI: 10.1080/00207590143000324
|View full text |Cite
|
Sign up to set email alerts
|

Attentional distraction and time perception in children

Abstract: The purpose of the present study was to test the effect of attentional distraction on temporal bisection performance in 5-and 8-year-old children. During a rst learning phase, children were trained to discriminate on a temporal bisection task a short standard duration (2 sec) from a long one (8 sec), presented as visual stimuli. Later, in a second testing phase, intermediate durations (3, 4, 5, 6, 7 s), including the standard durations, were presented. Children's task still was to report if it was a short stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 45 publications
4
18
0
Order By: Relevance
“…This is consistent with the result recently found in bisection by Zélanti and Droit-Volet (2011) who used more easily discriminable anchor durations and showed that the attention/executive function was the best predictor of age variance in sensitivity to time. This is also consistent with the results of experimental studies showing that the variability in children's time discrimination decreases when they are provided with a warning signal that improves the orientation of attention toward the stimulus duration to be processed, or a context with a reduced number of attentional distractors that improved the amount of attention devoted to time processing (Droit-Volet, 2003, 2011Gautier & Droit-Volet, 2002). This is also entirely consistent with studies that showed time disturbance in children with attention-deficit hyperactivity disorder (e.g., Huang et al, 2012;Rubia, Halari, Christakou, & Taylor, 2009;Smith et al, 2011;Smith, Taylor, Warner Rogers, Newman, & Rubia, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the result recently found in bisection by Zélanti and Droit-Volet (2011) who used more easily discriminable anchor durations and showed that the attention/executive function was the best predictor of age variance in sensitivity to time. This is also consistent with the results of experimental studies showing that the variability in children's time discrimination decreases when they are provided with a warning signal that improves the orientation of attention toward the stimulus duration to be processed, or a context with a reduced number of attentional distractors that improved the amount of attention devoted to time processing (Droit-Volet, 2003, 2011Gautier & Droit-Volet, 2002). This is also entirely consistent with studies that showed time disturbance in children with attention-deficit hyperactivity disorder (e.g., Huang et al, 2012;Rubia, Halari, Christakou, & Taylor, 2009;Smith et al, 2011;Smith, Taylor, Warner Rogers, Newman, & Rubia, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have shown the importance of attention for the processing of long durations (Coull et al, 2004;Lewis & Miall, 2009). So far as young children are concerned, when they estimate durations while performing a concurrent nontemporal task or in the presence of attentional distractors, they systematically produce shorter and more variable durations (Arlin, 1986;Droit-Volet et al, 2006;Gautier & Droit-Volet, 2002b;Zakay, 1992). These findings have been explained in terms of the lesser volume of attentional resources available to young children for the processing of temporal information.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, attentional functions largely depend on the prefrontal cortex, which develops slowly throughout childhood and into young adulthood (Casey, Tottenham, Liston, & Durston, 2005;Diamond, 2002;Tsujimoto, 2008). Furthermore, studies on time perception that have used both divided and distracting attention tasks have shown that the attention-related shortening effect is greater in 5-year-olds than in older children (Droit-Volet, Delgado, & Rattat, 2006;Gautier & Droit-Volet, 2002a, 2002bZakay, 1992). This explains why time estimation is often impaired in children with attention deficit hyperactivity disorder (ADHD) (e.g., Smith, Taylor, Rogers, Newman, & Rubia, 2002;Toplak, Dockstader, & Tannock, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…In addition, children's sensitivity to time appears to be lower for visual signals than for auditory signals, and this difference in the sensitivity to time between these two modalities decreases with age. Developmental studies have indicated that the lower sensitivity to time in young children was due mainly to their limited attention capacities (e.g., Droit-Volet, 2003, 2011Gautier & Droit-Volet, 2002a, 2002bZélanti & Droit-Volet, 2011). Therefore, we can suggest that the lower temporal sensitivity for visual signals than for auditory signals, which is more marked in young children, was in great part related to the heavy attentional demands on timing of visual stimuli.…”
Section: Introductionmentioning
confidence: 91%